Discussion of Papers Published Prior to 1957 - Precision Survey for Tunnel Control (1958) (211, p. 977) - D. D. Donald (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1960)
C. J. Barber (U. S. Smelting Refining & Mining Co., Salt Lake City)—In his paper Donald describes how New Jersey Zinc Co. made surveys for a connection between the Ivanhoe and Van Mater shafts at Austin-ville, Va. Except to say that the two faces had to meet "accurately" on line and grade, Donald does not indicate the required precision. Assuming that there were 24 angles in the 11/2-mile traverse and 15 in the one-mile traverse, it can be shown that if the average error in plumbing each shaft was 230" and the average error in measuring each traverse angle was 210". then the average error at the point of -connection would have been about ±1.9 ft normal to the line between the shafts. This calculation assumes that any errors in the triangulation would be negligible compared with the errors in the plumbings and traverses, and it also neglects taping errors. With no constant errors or blunders, the latter would be important only in lines normal to the line between the shafts. To make the average error at the connection less than 1.9 ft would, therefore, require either reducing the error in the plumbings to less than ±30", or that in the traverse angles to less than ±l0", or fewer stations, or a combination of these. Referring briefly to the triangulation, because of the problem of fitting a new triangulation into older surveys of the district the orientation deserved some mention, even though the connection could have been made with an assumed bearing. It would be interesting to know how many triangles were required and what the average summation error was before making any adjustments and without considering the algebraic signs. Perhaps this is referred to indirectly in the statement that the maximum angular error distributed was 2". Turning to the shaft plumbings, it would be helpful to know how many men were employed and how long each shaft was in use. Donald says that the surface positions of W-2 and W-3 were carefully surveyed from the collar position of W-1, without indicating how this was done. The length of the backsight would be particularly important. There must have been some error in setting W-1 vertically below the stations in the headframes. How immovable were the headframes, especially the Van Mater, which appears higher than the Ivanhoe and subject to more vibration because of skip hoisting? Donald does not say whether the plumbing wires had been previously restraightened to minimize spinning (otherwise they behave like weak helical springs). The use of light steel weights is most surprising because there seem to be excellent reasons for using heavier, nonmagnetic weights. Did the shafts contain no steel sets, pipes, power cables, etc., which might attract steel? The plumbing method described by Donald was designed for deep shafts in South Africa but differed from the South African practice in two important respects. As described by Browne,6 in South Africa the line between the wires was made parallel to the long axis of the shaft, whereas in the Ivanhoe shaft the lines between the wires were diagonally across the shaft. The main reason given for the South African practice is to insure that the gravitational attraction between the wires and the rock walls is the same on both wires, and therefore does not affect the bearing of the line between them. It seems probable, however, that the effect of air currents might be minimized in the South African procedure, and might be serious with the wires in the diagonal position at the Ivanhoe shaft. In the South African case cited by Donald the wires were swinging freely (although the plumb bobs were sheltered from air currents) but in the Ivanhoe case they were dampened with the plumb bobs set in water. In the discussion of Browne's paper R. St. J. Rowland said:' It has been the practice for a long time to damp the oscillations by immersing the bobs in oil or water. The time per oscillation is thus increased, thereby extending the time taken to complete the work. The longer the suspended wire the less there is to recommend the practice . . . The theoretical time for one swing of a simple pendulum 1050 ft long is approximately 36 sec, which would be increased by dampening the plumb bob in water. Hence very few complete swings would be observed in the 5 min intervals used at the Ivanhoe shaft. In the two South African cases described by Browne, the length of plumb line in one shaft was 5425 ft, the calculated period of swing was 81.6 sec, the average actual period was 76.6 sec, and 94 complete swings were observed in 2 hr. In the other case the length of plumb line was 3116 ft, the calculated period of swing was 61.8 sec, the average period was 63.5 sec, and 86 complete swings were observed in 1 hr 31 min. Browne concluded that observations of more than 30 swings are not likely to result in sufficient gain in accuracy to be justified. Returning to the Ivanhoe and Van Mater plumbings, an objection to the method used is that all four azimuths were taken from fixed points instead of swinging wires, and that each pair of observations would— barring blunders— check closely, and so perhaps give a false feeling of security. In fact, it seems that only two azimuths were obtained from one plumbing, and not four as stated by Donald. Nevertheless, the tying in of each pair of wires from both sides of the shaft has much to commend it. Donald's description leaves the impression that if each shaft was plumbed only once, the engineers were fortunate indeed if the average error in the underground orientation was as little as 30". Because the survey was done over a period of three years, it seems likely that the plumbings were repeated, perhaps more than once. The underground traverse angles were measured by conventional methods, but because the number of angles in the overlapping traverses was not given, the angular closure given by Donald does not indicate the accuracy with which this was done. Donald's description of a method of taping lines of irregular length is welcome. The literature on taping is usually confined to lines of about one tape length, generally 100 ft. Such lines are rare in metal mining because the time, trouble, and cost of setting points at 100-ft distances underground are not warranted. (Nevertheless civil engineers may go to this expense